2019
DOI: 10.3389/fimmu.2019.00556
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Immunosuppressive Drugs and Therapeutic Immunoglobulins Differentially Inhibit NK Cell Effector Functions in vitro

Abstract: Small-molecule immunosuppressive drugs (ISD) prevent graft rejection mainly by inhibiting T lymphocytes. Therapeutic immunoglobulins (IVIg) are used for substitution, antibody-mediated rejection (AbMR) and HLA-sensitized recipients by targeting distinct cell types. Since the effect of ISD and IVIg on natural killer (NK) cells remains somewhat controversial in the current literature, the aim of this comparative study was to investigate healthy donor's human NK cell functions after exposure to ISD and IVIg, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 83 publications
2
25
0
1
Order By: Relevance
“…The results suggest that the inhibitory effect of MMF/MPA on IL-2 activated NK cell function is a rather late event. In contrast, Pradier et al reported on a significant reduction of anti-tumor activity by NK cells which were pre-stimulated overnight with IL2 (50 U/mL) and IL12 (0.5 ng/mL) indicating that the pre-stimulation modifies the effect of immunosuppressive agents on NK cells [22].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The results suggest that the inhibitory effect of MMF/MPA on IL-2 activated NK cell function is a rather late event. In contrast, Pradier et al reported on a significant reduction of anti-tumor activity by NK cells which were pre-stimulated overnight with IL2 (50 U/mL) and IL12 (0.5 ng/mL) indicating that the pre-stimulation modifies the effect of immunosuppressive agents on NK cells [22].…”
Section: Discussionmentioning
confidence: 89%
“…Our results demonstrate that mPRED increases apoptosis and has a strong negative impact on the proliferation of human NK cells, whereas, no significant decrease in the anti-Aspergillus activity of human NK cells was observed. In contrast, it has been reported that mPRED decreases both the natural and receptor-mediated cytotoxicity of NK cells against various tumor cells lines [21,22]. The latter observation was explained by the inhibition of the surface expression of the Natural Cytotoxicity Receptors (NCR) NKp30 and NKp44.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…test statistic = 2.506929 p = 0.01218 i-Score prognosticates graft survival in LpAMR: The presence of interstitial inflammation comprising more than 25% of the biopsy core is associated with reduced graft survival immunosuppressants in renal transplantation (49). In comparison, cytokine production is suppressed by prednisone and calcineurin inhibitors, although not by mycophenolate mofetil (49).…”
mentioning
confidence: 99%